2015
DOI: 10.5194/bg-12-365-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification accelerates dissolution of experimental coral reef communities

Abstract: Abstract. Ocean acidification (OA) poses a severe threat to tropical coral reefs, yet much of what is know about these effects comes from individual corals and algae incubated in isolation under high pCO 2 . Studies of similar effects on coral reef communities are scarce. To investigate the response of coral reef communities to OA, we used large outdoor flumes in which communities composed of calcified algae, corals, and sediment were combined to match the percentage cover of benthic communities in the shallow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
67
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 43 publications
9
67
0
2
Order By: Relevance
“…This is supported by the observation of the highest MPB biomass in the center of the advective chambers, where the longest flow path of porewater emerge at the surface, thus supplying the highest nutrient load (Huettel and Gust, 1992). Similar to our study neither photosynthesis nor OM remineralization were affected by elevated pCO 2 in coral reef sediments in Heron Island (GBR, Australia, Anthony et al, 2013;Cyronak et al, 2013a;Cyronak and Eyre, 2016;Trnovsky et al, 2016) and Moorea (French Polynesia, Comeau et al, 2014Comeau et al, , 2015. However, in reef sediments from Sesoko Island (Okianwa, Japan) high pCO 2 stimulated photosynthesis and bacterial growth, while oxygen consumption was reduced (Sultana et al, 2016).…”
Section: Discussion Elevated Pco 2 Does Not Affect Biotic Processessupporting
confidence: 90%
See 1 more Smart Citation
“…This is supported by the observation of the highest MPB biomass in the center of the advective chambers, where the longest flow path of porewater emerge at the surface, thus supplying the highest nutrient load (Huettel and Gust, 1992). Similar to our study neither photosynthesis nor OM remineralization were affected by elevated pCO 2 in coral reef sediments in Heron Island (GBR, Australia, Anthony et al, 2013;Cyronak et al, 2013a;Cyronak and Eyre, 2016;Trnovsky et al, 2016) and Moorea (French Polynesia, Comeau et al, 2014Comeau et al, , 2015. However, in reef sediments from Sesoko Island (Okianwa, Japan) high pCO 2 stimulated photosynthesis and bacterial growth, while oxygen consumption was reduced (Sultana et al, 2016).…”
Section: Discussion Elevated Pco 2 Does Not Affect Biotic Processessupporting
confidence: 90%
“…Experimental studies showed that the reductions in will decrease the net ecosystem calcification (NEC) of coral reefs, turning them from a state of net precipitation to a state of net dissolution, with potentially negative consequences for the role and function of reef ecosystems (Andersson and Gledhill, 2013). The expected reductions in NEC are caused by lower rates of calcification (e.g., Leclercq et al, 2002;Langdon et al, 2003;Andersson et al, 2009;Dove et al, 2013) and by increased dissolution rates of existing carbonate structures, including reef sediments (e.g., Andersson et al, 2009;Anthony et al, 2013;Cyronak et al, 2013a;Comeau et al, 2015). Even though much less studied, recent data suggests that the increase in dissolution may be more sensitive to OA than the decrease in calcification .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of processes such as dissolution of reef CaCO 3 sediments (e.g., Yates and Halley, 2006;Andersson et al, 2007Andersson et al, , 2009Tribollet et al, 2009;Rao et al, 2012;Comeau et al, 2015;Rodolfo-Metalpa et al, 2015;Yamamoto et al, 2015), pore water and alkalinity fluxes from the sediment (e.g., Falter and Sansone, 2000;Santos et al, 2011Santos et al, , 2012aCyronak et al, 2013a,b), and coral bioerosion (e.g., Wisshak et al, 2012;Crook et al, 2013;Enochs et al, 2015;Kline et al, 2015) all contribute to elucidating the complex controls and responses of coral reefs to changes in ocean chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of OA studies have been performed ex situ at the cellular (e.g., Cohen and Holcomb, 2009;Venn et al, 2013), organismal (e.g., Ries et al, 2009;Erez et al, 2011), and community scales (e.g., Andersson et al, 2009;Comeau et al, 2015), and have manipulated seawater pCO 2 or pH to simulate future ocean conditions and measured rates of net production (P) and net calcification (G) as response variables. On average, the response of taxon-specific G to OA predict that G in tropical marine calcifiers will decrease 14-30% by 2100 (Chan and Connolly, 2013;Kroeker et al, 2013), while P has been mostly predicted to be unaffected (Schneider and Erez, 2006;Kroeker et al, 2013;Comeau et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On average, the response of taxon-specific G to OA predict that G in tropical marine calcifiers will decrease 14-30% by 2100 (Chan and Connolly, 2013;Kroeker et al, 2013), while P has been mostly predicted to be unaffected (Schneider and Erez, 2006;Kroeker et al, 2013;Comeau et al, 2015). Likewise, seawater warming studies performed ex situ at the organismal scale (e.g., Reynaud et al, 2003;Comeau et al, 2016a) show that G and P in tropical marine calcifiers is enhanced until a threshold temperature (∼28 • C in many organisms, but highly site specific; Pratchett et al, 2015) and then dramatically decreases thereafter due, in part, to bleaching or mortality (Hughes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%